Glycyrrhizin Suppresses the Growth of Human NSCLC Cell Line HCC827 by Downregulating HMGB1 Level. (15th January 2018) - Wu, Xiaojin; Wang, Weitao; Chen, Yuanyuan; Liu, Xiangqun; Wang, Jindong; Qin, Xiaobin; Yuan, Dawei; Yu, Tao; Chen, Guangxia; Mi, Yanyan; Mou, Jie; Cui, Jinpeng; et al.
Abstract : Lung cancer has very high mortality and glycyrrhizin was found to significantly inhibit the growth of lung cancer cells in vitro and tissues in mice. However, the detailed inhibitory role of glycyrrhizin in the growth of lung cancer is still unclear. In this study, we first found that glycyrrhizin inhibited the growth of lung tumor in PDX mice. And high level of HMGB1 promoted the migration and invasion of lung cancer cells, which was suppressed by glycyrrhizin. Moreover, glycyrrhizin reduced the activity of JAK/STAT signaling pathway, which is the upstream regulator of HMGB1. Therefore, this study revealed a potential mechanism by which glycyrrhizin can inhibit the progression of lung cancer.